Phase II clinical study of irinotecan and cisplatin as first-line chemotherapy in metastatic or recurrent cervical cancer - Chitapanarux I. (2014)
Objective. The goal of this study was to evaluate the efficacy and tolerability of irinotecan plus cisplatin as first-line chemotherapy in metastatic or recurrent cervical cancer. Methods. Chemotherapy-naive patients with metastatic or recurrent disease and at least one measurable tumor site received irinotecan (60 mg/m2 IV infusion over 90 min) on Days 1, 8, and 15, followed by cisplatin (60 mg/m2 IV over 90 min) on Day 1, every 28 days for a maximum of six cycles. Results. Thirty patients were included in the response and toxicity analysis. The median age was 45 years (34-65). Nineteen patients had metastatic disease, 6 presented with locally recurrent disease, and 5 presented with locally recurrent plus metastatic disease. Seven patients were stage IVB at diagnosis. There were 2 complete and 18 partial responses and overall response rate was 66.7% (95% confidence interval: 47-85%). Stable disease was observed in 2 patients (6.7%) and progression in 8 (26.7%). Median time to relapse was 13.4 months, with a median survival time of 16.9 months. One-year disease-free survival and overall survival were 26.7 and 65.1%, respectively. Dose-limiting toxicity was observed in 4 patients (13.3%) with grade 3 renal toxicity. Nine patients (30%) developed grade 3 neutropenia, and only grade 1-2 acute and late diarrhea were observed in 20 and 40%, respectively. A patient developed pancolitis after the sixth cycle. There were no chemotherapy-related deaths. Conclusion. The combination of irinotecan and cisplatin is a clinically active regimen for metastatic and/or recurrent cervical cancer with acceptable tolerability. © 2003 Elsevier Science (USA). All rights reserved.